Positive electrode material and battery

By controlling the average aspect ratio of the particles of the cathode material and the proportion of the number of particles with a particle size less than 1 μm, the roundness and compaction density of the cathode material are improved, and the existing cathode materials have high activity, easy gas production and short cycle life in battery reactions are solved, and the effects of high capacity, energy density and long cycle stability are achieved.

CN119764411APending Publication Date: 2025-04-04SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411976302.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing positive electrode materials are highly active in battery reactions and are easy to react with electrolytes, resulting in degradation of material gas production, cycle life and high-temperature storage performance.

Method used

By controlling the average length-to-diameter ratio of the particles of the positive electrode material within the range of 1≤α≤1.6, the roundness of the particles is improved, local stress accumulation is reduced, and the compaction density and capacity are improved by adjusting the proportion of particles with a particle size less than 1 μm.

Benefits of technology

The high capacity and energy density of the cathode material are achieved, excellent long cycle stability, especially the cycle stability under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764411A_ABST
    Figure CN119764411A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material and a battery. The positive electrode material comprises a plurality of particles, an SEM image of the positive electrode material is measured under the amplification factor of 3K through a scanning electron microscope, 200 particles in the SEM image are measured randomly, the average size of the longest diameter of a single particle is D, the average size of the width diameter vertically equally dividing the longest diameter of the particle is L, the average length-diameter ratio alpha of the particles is equal to D / L, and alpha is larger than or equal to 1 and smaller than or equal to 1.6; and in the positive electrode material, the number ratio of particles with the particle size of less than 1 mu m is R%, and R is more than or equal to 10 and less than or equal to 16. The positive electrode material provided by the invention has high capacity and energy density, and excellent long cycle stability, especially high-temperature cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and batteries. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, high power density, long cycle life and low self-discharge, so they are widely used in 3C electronic products, electric vehicles and energy storage. As the core component of lithium-ion batteries, the positive electrode material directly determines the operating voltage and storage capacity of the battery.

[0003] At present, positive electrode materials have high activity in battery reactions and are easy to react with electrolytes, resulting in defects such as gas production, decreased cycle life, and high-temperature storage performance. Therefore, how to make positive electrode materials have excellent capacity and energy density and improve the long-cycle stability of positive electrode materials is still an urgent problem to be solved. Summary of the invention

[0004] The present application provides a positive electrode material and a battery. The positive electrode material of the present application has both high capacity and energy density, and excellent long-cycle stability, especially high-temperature cycle stability.

[0005] In a first aspect, the present application provides a positive electrode material; the positive electrode material comprises a plurality of particles;

[0006] The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the wide diameter that perpendicularly divides the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.6;

[0007] In addition, the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, and 10≤R≤16.

[0008] In some embodiments, the chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.5≤a≤0.98, 0<b≤0.40, 0<c≤0.4, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al; the M element includes at least one of Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.

[0009] In some embodiments, in the positive electrode material, the number of particles satisfying 1≤α≤1.6 accounts for ≥90% of all particles.

[0010] In some embodiments, the volume median particle size D50 of the positive electrode material is 2.0 μm to 6.0 μm; and / or the volume particle size distribution width of the positive electrode material satisfies: 1.0<(D 90 -D 10 ) / D 50 ≤2.

[0011] In some embodiments, the positive electrode material is a single crystal material, the particles include primary particles, and the particle size of the primary particles is 1 μm to 5 μm.

[0012] In some embodiments, the specific surface area of ​​the positive electrode material is 0.4 m 2 / g~0.8m 2 / g.

[0013] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 1.5≤ρ1<2.2.

[0014] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 3.0≤ρ2<3.5.

[0015] In some embodiments, the positive electrode material satisfies 11≤pH≤12.

[0016] In some embodiments, the button-type battery made of the positive electrode material has a capacity retention rate of ≥95% after cycling for 50 weeks at 55°C.

[0017] In a second aspect, the present application provides a battery, comprising the positive electrode material described in the first aspect.

[0018] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0019] The average aspect ratio of the particles of the positive electrode material of the present application is within the above range, the roundness of the particles is improved, and there are no obvious edges and corners, which is conducive to the uniform dispersion of the particle expansion stress, reducing local stress accumulation, and improving the structural stability and cycle capacity retention rate of the positive electrode material; at the same time, the specific surface area of ​​the positive electrode material can be reduced, and the surface energy of the particles is relatively low, which can reduce the side reaction between the positive electrode material and the electrolyte, so that the long cycle performance is improved. However, with the improvement of the roundness of the particles, the fine powder is reduced, and the volume particle size distribution of the positive electrode material is narrowed, which will cause the compaction density of the positive electrode material to decrease and the capacity to decrease. Therefore, while controlling the average aspect ratio of the positive electrode material particles, the present application controls the number of particles of 1μm to be within a suitable range. These particles with a particle size of less than 1μm can be effectively filled in the gaps between particles greater than 1um, thereby improving the compaction density and capacity of the positive electrode material, and the particles with a large number and good roundness can reduce the particle rupture of the positive electrode material and improve the structural stability and long cycle performance of the positive electrode material. Under the synergistic effect of the two, the positive electrode material has both high capacity and energy density, and excellent long cycle stability, especially high temperature cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0021] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.

[0022] Figure 2 This is a SEM morphology image of the positive electrode material provided in Example 1 of the present application.

[0023] Figure 3 This is a SEM morphology image of the positive electrode material provided in Comparative Example 1 of the present application.

[0024] Figure 4 This is a comparison chart of the positive electrode material cycle performance provided by Example 1 of the present application and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0025] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0026] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0028] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0029] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a plurality of particles;

[0030] The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the wide diameter that perpendicularly divides the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.6;

[0031] In addition, the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, and 10≤R≤16.

[0032] The average aspect ratio of the particles of the positive electrode material of the present application is within the above range, the roundness of the particles is improved, and there are no obvious edges and corners, which is conducive to the uniform dispersion of the particle expansion stress, reducing local stress accumulation, and improving the structural stability and cycle capacity retention rate of the positive electrode material; at the same time, it can also reduce the specific surface area of ​​the positive electrode material, and the surface energy of the particles is relatively low, which can reduce the side reaction between the positive electrode material and the electrolyte, so that the long cycle performance is improved. However, with the improvement of the roundness of the particles, the fine powder is reduced, and the volume particle size distribution of the positive electrode material is narrowed, which will cause the compaction density of the positive electrode material to decrease and the capacity to decrease. Therefore, while controlling the average aspect ratio of the positive electrode material particles, the present application controls the number of particles of 1μm to be within a suitable range. These particles with a particle size less than 1μm can be effectively filled between particles with an aspect ratio of 1 to 1.6, which can improve the compaction density and capacity of the positive electrode material. The particles with a large number and good roundness can reduce the particle rupture of the positive electrode material and improve the structural stability and long cycle performance of the positive electrode material. Under the synergistic effect of the two, the positive electrode material has both high capacity and energy density, and excellent long-cycle stability, especially high-temperature cycle stability. It should be noted that when the average aspect ratio of the positive electrode material particles is too large, it means that the particles are poorly rounded and have obvious edges and corners. It is easy to produce more fine powder during the particle shaping process, resulting in an increase in the specific surface area of ​​the positive electrode material and an increase in side reactions with the electrolyte.

[0033] In some embodiments, the positive electrode material has the general chemical formula Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.40, 0<c≤0.4, 0≤d≤0.10, N is Mn or Al, and M is a metal element.

[0034] The specific value of x can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the specific value of a can be 0.5, 0.6, 0.7, 0.8, 0.82, 0.84, 0.85, 0.88, 0.89, 0.90, 0.92, 0.95 or 0.98, and the value of b can be 0.001, 0.01, 0.05, 0.1, 0.15, 0 .16, 0.2, 0.25, 0.3, 0.35 or 0.4, the value of c can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.2, 0.25, 0.3, 0.35 or 0.4, the value of d can be 0, 0.001, 0.005, 0.006, 0.008, 0.009, 0.01, 0.02, 0.03, 0.05, 0.07 or 0.1, etc., and is not limited here.

[0035] In some embodiments, the M element includes at least one of Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y. It can be understood that an appropriate amount of M element doping can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing.

[0036] In some embodiments, the average aspect ratio of the particles satisfies 1≤α≤1.6, and can be specifically 1, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55 or 1.6, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The average aspect ratio of the particles is within the above range, the particles have high roundness and no obvious edges and corners, which is conducive to reducing the specific surface area of ​​the positive electrode material, reducing the direct contact between the positive electrode material and the electrolyte, and reducing the occurrence of side reactions. And the aspect ratio is controlled within the above range, which is conducive to the uniform dispersion of the particle expansion stress, reducing local stress accumulation, and improving the structural stability of the positive electrode material.

[0037] In some embodiments, 1μm<D<5μm, 1μm<L<5μm. The value of D can be 1.1μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm or 4.9μm, etc., and of course it can also be other values ​​within the above range, which is not limited here. The value of L can be 1.1μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm or 4.9μm, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0038] In some embodiments, in the positive electrode material, the number of particles satisfying 1≤α≤1.6 in all particles accounts for P%, P≥90, which can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, etc., and of course it can also be other values ​​within the above range, which are not limited here. It can be understood that the higher the number of particles with high roundness, the lower the number of elongated particles in the positive electrode material, which is conducive to the uniform dispersion of particle expansion stress, and the lithium ion deintercalation rate can remain isotropic, which is conducive to improving the rate performance and cycle capacity retention rate of the positive electrode material. It should be noted that particles with a particle size of less than 1μm can also meet 1≤α≤1.6. These small and round particles can be filled between particles with large particle sizes, which can increase the compaction density of the positive electrode material and thus increase the energy density of the battery.

[0039] In some embodiments, the volume median particle size D50 of the positive electrode material is 2.0 μm to 6.0 μm, specifically 2.0 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm or 6.0 μm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Since the volume median particle size of the positive electrode material is within the above range, the particles within this size range have better electrochemical properties, higher discharge capacity and excellent rate performance.

[0040] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 1.0<(D 90 -D 10 ) / D 50 ≤2, specifically 1.05, 1.08, 1.1, 1.15, 1.18, 1.2, 1.22, 1.25, 1.26, 1.3, 1.35, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, etc., and of course, other values ​​within the above range are also possible, which are not limited here. In the present application, by controlling the particle size distribution width of the positive electrode material within the above range, particles of different sizes can be stacked more closely, so that the compaction density of the positive electrode sheet is improved and the energy density is higher.

[0041] In some embodiments, the positive electrode material is a single crystal material, the particles include primary particles, and the particle size of the primary particles is 1 μm to 5 μm.

[0042] It should be specifically pointed out that the "grains with the same orientation" known to those skilled in the art are not "single crystals" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in reality. Therefore, the materials known in the art that have a single crystal structure are actually more of a "single crystal-like morphology" positive electrode material, which only shows a single crystal-like large particle size in size, which is different from the polycrystalline particles composed of many small particles.

[0043] The particles with the same orientation in the present application can be a single particle composed of one primary particle. The above-mentioned single crystal positive electrode material can also contain a small amount of "quasi-secondary particles" formed by the adhesion of several primary particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope.

[0044] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one primary particle is the same, so as to judge that the orientation in at least one primary particle is the same, and the primary particles with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0045] In some embodiments, the specific surface area of ​​the positive electrode material is 0.4 m 2 / g~0.8m 2 / g. Specifically, it can be 0.4m2 / g, 0.45m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.75m 2 / g or 0.8m 2 / g, etc., and of course, other values ​​within the above range may also be used, which are not limited here. Thanks to the improved roundness of the particles in the positive electrode material, the specific surface area of ​​the positive electrode material can be controlled within the above range, which can effectively reduce the side reaction between the positive electrode material and the electrolyte and improve the capacity of the positive electrode material.

[0046] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 1.5≤ρ1<2.2, specifically 1.91g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 or 2.69 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here.

[0047] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 3.0≤ρ2<3.5. Specifically, it can be 3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.25g / cm 3 、3.3g / cm 3 、3.35g / cm 3 、3.4g / cm 3 、3.45g / cm 3 or 3.49 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here.

[0048] In some embodiments, the positive electrode material satisfies 11≤pH≤12, which can be specifically 11, 11.2, 11.5, 11.7, 11.8, 11.9 or 12, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. It can be understood that the surface alkaline impurities of the positive electrode material mainly refer to Li2CO3 and LiOH. When the pH value of the positive electrode material is within the above range, the gas production of the positive electrode material during the cycle can be reduced, the structural stability of the positive electrode material can be protected, and the cycle stability of the positive electrode material can be improved.

[0049] In some embodiments, the button battery made of the positive electrode material has a capacity retention rate of ≥95% after 50 cycles at 55°C, which can be specifically 95%, 95.5%, 95.8%, 96.2%, 96.5%, 97.0%, 97.5%, 98.0%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0051] Step S100, mixing a precursor, a lithium salt and a dopant to obtain a first mixture, wherein the dopant includes at least one of compounds of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y;

[0052] In some embodiments, the precursor has the general chemical formula Ni x Co y N z O2, wherein 0.6≤x≤0.98, 0<y≤0.4, 0<z≤1-xy, and the N element is Mn or Al.

[0053] In some embodiments, the precursor has the general chemical formula Ni x Co y N z (OH)2, wherein 0.6≤x≤0.98, 0<y≤0.4, 0<z≤1-xy, and the N element is Mn or Al.

[0054] In some embodiments, the median particle size of the precursor is 2.0 μm to 4.0 μm, specifically 2.0 μm, 2.3 μm, 2.5 μm, 3.0 μm, 3.5 μm, 3.8 μm, 3.9 μm or 4.0 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some embodiments, the dopant may be an oxide, a salt, etc. of the above elements, which is not limited herein.

[0056] In some embodiments, the amount of dopant added is 0.05% to 0.5%, specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.28%, 0.3%, 0.4% or 0.5%, etc., based on the mass of the nickel-cobalt-manganese-based oxide precursor as 100%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The amount of dopant added in the present application is controlled within the above range, which is beneficial to control the size of the primary particles of the positive electrode material and the arrangement of the primary particles, and improve the capacity and particle structure stability of the positive electrode material.

[0057] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium chloride, lithium nitrate, and lithium oxalate.

[0058] In some embodiments, the ratio of the molar amount of Li in the first mixture to the total molar amount of transition metal in the precursor is controlled to be 0.98≤n Li / n Me ≤1.1; specifically, it can be 0.98:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.08:1 or 1.1:1, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0059] In some embodiments, the mixing is performed in a mixing device, which may be a high-speed mixer, a ball mill mixer, a VC mixer, or a three-dimensional mixer, etc. The device may be selected according to actual needs and is not limited here.

[0060] In some embodiments, mixing includes low-speed mixing, medium-speed mixing and high-speed mixing. By gradually increasing the mixing speed, it is possible to ensure that the components are mixed evenly, which is beneficial to improving the distribution uniformity of the nickel-cobalt-manganese-based oxide precursor, the lithium source and the dopant, and is beneficial to reducing structural defects in the positive electrode material and improving the structural orderliness of the positive electrode material.

[0061] Step S200 , performing a pre-oxidation sintering treatment on the first mixture in an oxygen-containing atmosphere to obtain a pre-oxidation composite.

[0062] In some embodiments, the first mixture is pressed into a compacted material, and then punched with holes, with the spacing between the holes being controlled to be less than 1 cm.

[0063] In some embodiments, the temperature of the pre-oxidation sintering treatment is 500°C to 900°C, specifically 500°C, 550°C, 570°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0064] In some embodiments, the ambient pressure during the pre-oxidation sintering treatment is 20Pa to 60Pa, specifically 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, 50Pa, 55Pa or 60Pa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0065] In some embodiments, the pre-oxidation sintering treatment time is 2 h to 8 h, specifically 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0066] In the present application, the first mixture is first subjected to a pre-oxidation sintering treatment. By controlling the pressure, temperature and time, the lithium salt can act as a flux to make the various components mixed more evenly. The lithium ions in the lithium salt are embedded in the precursor, which can improve the roundness of the precursor particles. At the above temperature, most of the lithium salt can be embedded in the precursor, which can reduce the residual lithium salt and the generation of fine powder to obtain a pre-oxidation composite.

[0067] Step S300, mixing the pre-oxidized composite with the oxygen supplement to obtain a second mixture, and subjecting the second mixture to a pulse sintering in an oxygen-containing atmosphere to obtain a matrix material, wherein the pulse sintering includes a first stage, a second stage, the first stage and the second stage repeated, and a fifth stage, the sintering temperature T1 of the first stage is 800°C to 1000°C, the sintering temperature T2 of the second stage is T1-30°C, and the sintering temperature T5 of the fifth stage is T2-10°C; the total holding time for controlling the T1 temperature is 4h to 8h.

[0068] In some embodiments, the oxygen supplement includes at least one of lithium peroxide, sodium peroxide, sodium perborate and potassium permanganate. It is understandable that the oxygen supplement can decompose at high temperature to generate oxygen. Since the oxygen supplement is fully mixed with the pre-oxidation composite, the oxygen supplement can be filled between the pre-oxidation composite particles, and in the subsequent pulse sintering process, additional oxygen is provided, which is conducive to the full oxidation of each component.

[0069] In some embodiments, based on the mass of the pre-oxidation composite being 100%, the amount of oxygen supplement added is 0.5% to 1%, specifically 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] It can be understood that the pre-oxidation composite particles are relatively compact, and it is difficult for oxygen to penetrate during a single pulse sintering process. Therefore, an oxygen supplement is added. The oxygen supplement decomposes at high temperature to produce oxygen with few by-products. It can provide the oxygen required for the pre-oxidation composite to continue to be fully oxidized from within the second mixture, making the single pulse sintering more complete and improving the structural stability of the matrix material.

[0071] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere is ≥ 90%.

[0072] In some embodiments, the heating rate of a pulse sintering is 0.5°C / min to 2.5°C / min, specifically 0.5°C / min, 0.75°C / min, 1°C / min, 1.25°C / min, 1.5°C / min, 2°C / min, 2.25°C / min or 2.5°C / min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0073] In some embodiments, during a pulse sintering process, the ambient pressure is 20Pa to 60Pa, specifically 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, 50Pa, 55Pa or 60Pa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0074] In some embodiments, during a pulse sintering process, the sintering temperature T1 of the first stage is 800°C to 1000°C, and specifically can be 800°C, 820°C, 830°C, 850°C, 870°C, 900°C, 950°C, 980°C, 990°C or 1000°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0075] In some embodiments, during a pulse sintering process, the insulation time of the first stage is 1 h to 2 h, specifically 1.0 h, 1.2 h, 1.5 h or 2 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0076] In some embodiments, during a pulse sintering process, the sintering temperature T2 of the second stage is T1-30°C, specifically 770°C, 820°C, 850°C, 870°C, 900°C, 950°C or 970°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0077] In some embodiments, during a pulse sintering process, the insulation time of the second stage is 1 h to 2 h, specifically 1.0 h, 1.2 h, 1.5 h or 2 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0078] In some embodiments, during a pulse sintering process, the total holding time for controlling the temperature of T1 is 4 to 8 hours, which can be 4.0 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The total holding time for controlling the temperature of T2 is 4 to 8 hours, which can be 4.0 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0079] In some embodiments, during a pulse sintering process, the sintering temperature T4 of the fourth stage is T2-10°C, i.e., 760°C to 960°C, specifically 760°C, 820°C, 850°C, 870°C, 900°C, 950°C or 960°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0080] In some embodiments, the insulation time of the fourth stage is 4 h to 6 h, specifically 4 h, 4.5 h, 5 h, 5.5 h, 5.8 h or 6 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0081] During a pulse sintering process, the temperature and time of the fourth stage are controlled within the above range, which can promote the repair of the grain boundary surface of the primary particles of the positive electrode material and improve the particle tolerance and structural order of the positive electrode material.

[0082] Step S300, the base material is subjected to micron-scale particle dissociation treatment, the dissociation product is mixed with a coating agent, and then subjected to secondary sintering treatment to obtain a positive electrode material.

[0083] In some embodiments, the dissociation treatment comprises at least one of air flow milling and grinding.

[0084] In some embodiments, the grinding air pressure during air flow milling ranges from 0.3 MPa to 0.8 MPa, specifically 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.55 MPa, 0.6 MPa, 0.65 MPa, 0.7 MPa or 0.8 MPa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0085] In some embodiments, the classification frequency during air flow grinding is 30 Hz to 55 Hz, specifically 30 Hz, 35 Hz, 40 Hz, 45 Hz, 50 Hz or 55 Hz, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0086] In some embodiments, the average aspect ratio of the matrix material after the dissociation treatment is 1-1.6, and the number of particles with a particle size of less than 1 μm identified under a 3K electron microscope photograph accounts for 10% to 16%.

[0087] In some embodiments, based on the mass of the base material as 100%, the added amount of the coating agent is 0.05% to 0.4%, specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.28%, 0.3%, 0.35% or 0.4%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In some embodiments, the coating agent includes a compound containing an M element, and the M element includes at least one of compounds of B, Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.

[0089] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.

[0090] In some embodiments, the temperature of the secondary sintering treatment is 500°C to 900°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0091] In some embodiments, the time for the secondary sintering treatment is 6 h to 16 h, specifically 6 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or 16 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0092] In some embodiments, during the secondary sintering process, the ambient pressure is 20Pa to 60Pa, specifically 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, 50Pa, 55Pa or 60Pa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0093] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.

[0094] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.

[0095] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.

[0096] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.

[0097] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0098] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .

[0099] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.

[0100] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.

[0101] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0102] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0103] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0104] Example 1

[0105] (1) Weigh the chemical formula Ni 0.6 Co 0.1 Mn 0.3 2.5 kg of (OH)2 precursor, 1.2 kg of LiOH, 0.3% of ZrO2, 0.1% of Al2O3, and 0.1% of Sr(OH)2 based on the mass of the precursor are respectively added into a high-speed mixer. After the addition is completed, turn on the high-speed mixer and mix at a low speed (300 rpm) for 5 min; a medium speed (800 rpm) for 10 min; and a high speed (1500 rpm) for 15 min to obtain a first mixture.

[0106] (2) The first mixture is placed in a sintering vessel and pressed with a pressure of about 1 t to compact the material; holes are punched in the pressed material, and the spacing between the holes should be less than 1 cm; the punched material is placed in a kiln and pre-oxidized and sintered in an oxygen atmosphere at a temperature of 600°C, a furnace pressure of about 50 Pa, and a pre-oxidation and sintering time of 5 hours to obtain a pre-oxidized composite.

[0107] (3) Mixing the pre-oxidized composite with an oxygen supplement (lithium peroxide, the amount of lithium peroxide added is 1% based on the mass of the pre-oxidized composite) under nitrogen protection for 10 minutes to obtain a second mixture; placing the second mixture in a kiln and performing a pulse sintering in an oxygen atmosphere at a furnace pressure of 50 Pa; the pulse sintering steps include 960°C-2h→930°C-2h→960°C-2h→930°C-2h→960°C-2h→930°C-2h→960°C-2h→930°C-2h→960°C-2h→930°C-2h→920°C-4h to obtain a primary sintered product.

[0108] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.65 MPa and a grading frequency of 45 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 3.0 μm ≤ D50 ≤ 3.4 μm.

[0109] (5) The base material is mixed with 0.1% tungsten oxide and 0.1% titanium oxide under a nitrogen atmosphere to obtain a third mixture, and the third mixture is placed in a kiln for secondary sintering treatment under an oxygen atmosphere. The secondary sintering temperature is controlled to be 500°C, the furnace pressure is about 50 Pa, and the secondary sintering time is 10 hours to obtain a positive electrode material.

[0110] Figure 2 This is a SEM morphology of the positive electrode material provided in Example 1 of the present application, such as Figure 2 As shown, the chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0111] Example 2

[0112] The difference from Example 1 is:

[0113] The precursor in step (1) is generally Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0114] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.50 Co 0.2 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0115] Example 3

[0116] The difference from Example 1 is:

[0117] The precursor in step (1) is generally Ni 0.7 Co 0.1 Mn 0.2 (OH)2.

[0118] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.70 Co 0.1 Mn 0.2O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0119] Example 4

[0120] The difference from Example 1 is:

[0121] The precursor in step (1) is generally Ni 0.6 Co 0.1 Mn 0.3 O 2, The lithium salt used was anhydrous LiOH.

[0122] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.70 MPa and a grading frequency of 45 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 2.9 μm ≤ D50 ≤ 3.3 μm.

[0123] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0124] Example 5

[0125] The difference from Example 1 is:

[0126] The precursor in step (1) is generally Ni 0.8 Co 0.1 Mn 0.1 (OH)2.

[0127] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.70 MPa and a grading frequency of 45 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 2.9 μm ≤ D50 ≤ 3.3 μm.

[0128] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.80 Co 0.1 Mn 0.1 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0129] Example 6

[0130] The difference from Example 1 is:

[0131] The precursor in step (1) is generally Ni 0.98 Co0.01 Mn 0.01 (OH)2.

[0132] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.70 MPa and a grading frequency of 45 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 2.9 μm ≤ D50 ≤ 3.3 μm.

[0133] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.98 Co 0.01 Mn 0.01 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0134] Example 7

[0135] The difference from Example 1 is:

[0136] (2) The first mixture is placed in a sintering vessel and pressed with a pressure of about 1 t to compact the material; holes are punched in the pressed material, and the spacing between the holes should be less than 1 cm; the punched material is placed in a kiln for pre-oxidation sintering in an oxygen atmosphere, the pre-oxidation sintering temperature is 700°C, the furnace pressure is about 50 Pa, and the pre-oxidation sintering time is 8 hours to obtain a pre-oxidation composite.

[0137] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0138] Example 8

[0139] The difference from Example 1 is:

[0140] (1) Weigh the chemical formula Ni 0.6 Co 0.1 Mn 0.3 2.5 kg of (OH)2 precursor, 1.2 kg of LiOH, 0.3% of ZrO2, 0.1% of Al2O3, 0.1% of Sr(OH)2, and 0.05% of WO3 were weighed based on the mass of the precursor; added into a high-speed mixer respectively, and after adding, turned on the high-speed mixer and mixed at a low speed (300 rpm) for 5 minutes; a medium speed (800 rpm) for 10 minutes; and a high speed (1500 rpm) for 15 minutes to obtain a first mixture.

[0141] (2) The first mixture is placed in a sintering vessel and pressed with a pressure of about 1 t to compact the material; holes are punched in the pressed material, and the spacing between the holes should be less than 1 cm; the punched material is placed in a kiln for pre-oxidation sintering in an oxygen atmosphere, the pre-oxidation sintering temperature is 700°C, the furnace pressure is about 50 Pa, and the pre-oxidation sintering time is 2 hours to obtain a pre-oxidation composite.

[0142] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.6 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al, Sr and W, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0143] Example 9

[0144] The difference from Example 1 is:

[0145] In step (1), weigh the chemical formula Ni 0.6 Co 0.1 Al 0.3 2.5 kg of (OH)2 precursor, 1.2 kg of LiOH, 0.3% of ZrO2 and 0.1% of Sr(OH)2 based on the mass of the precursor were weighed and added into a high-speed mixer. After the addition was completed, the high-speed mixer was turned on and mixed at a low speed (300 rpm) for 5 min; a medium speed (800 rpm) for 10 min; and a high speed (1500 rpm) for 15 min to obtain a first mixture.

[0146] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Al 0.3 O2, where the doping elements are Zr and Sr. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0147] Example 10

[0148] The difference from Example 1 is that: in step (3), the pre-oxidized composite and the oxygen supplement (lithium peroxide, the amount of lithium peroxide added is 1% based on the mass of the pre-oxidized composite) are mixed under nitrogen protection for 10 minutes to obtain a second mixture; the second mixture is placed in a kiln and subjected to a pulse sintering in an oxygen atmosphere at a furnace pressure of 50 Pa; the pulse sintering steps include 960°C-4h→930°C-4h→960°C-4h→930°C-4h→920°C-4h to obtain a primary sintering product.

[0149] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0150] Embodiment 11

[0151] The difference from Example 1 is:

[0152] (3) Mixing the pre-oxidized composite with an oxygen supplement (lithium peroxide, the amount of lithium peroxide added is 1% based on the mass of the pre-oxidized composite) under nitrogen protection for 10 minutes to obtain a second mixture; placing the second mixture in a kiln for a pulse sintering in an oxygen atmosphere at a furnace pressure of 50 Pa; the pulse sintering steps include 960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→960°C-1h→930°C-1h→920°C-4h to obtain a primary sintered product.

[0153] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.70 MPa and a grading frequency of 50 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 3.0 μm ≤ D50 ≤ 3.4 μm.

[0154] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0155] Example 12

[0156] The difference from Example 1 is:

[0157] (3) Mixing the pre-oxidized composite with an oxygen supplement (sodium peroxide, lithium peroxide added in an amount of 0.5% based on the mass of the pre-oxidized composite) under nitrogen protection for 10 minutes to obtain a second mixture; placing the second mixture in a kiln and performing a pulse sintering in an oxygen atmosphere at a furnace pressure of 50 Pa; the pulse sintering steps include 960°C-2h→930°C-2h→960°C-2h→930°C-2h→960°C-2h→930°C-2h→960°C-2h→930°C-2h→960°C-2h→930°C-2h→920°C-4h to obtain a primary sintered product.

[0158] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.75 MPa and a grading frequency of 55 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 3.0 μm ≤ D50 ≤ 3.4 μm.

[0159] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0160] Embodiment 13

[0161] (1) Weigh the chemical formula Ni 0.6 Co 0.1 Al 0.3 2.5 kg of (OH)2 precursor and 1.2 kg of LiOH were added into a high-speed mixer. After the addition was completed, the high-speed mixer was turned on and mixed at a low speed (300 rpm) for 5 min; a medium speed (800 rpm) for 10 min; and a high speed (1500 rpm) for 15 min to obtain a first mixture.

[0162] (2) The first mixture is placed in a sintering vessel and pressed with a pressure of about 1 t to compact the material; holes are punched in the pressed material, and the spacing between the holes should be less than 1 cm; the punched material is placed in a kiln and pre-oxidized and sintered in an oxygen atmosphere at a temperature of 600°C, a furnace pressure of about 50 Pa, and a pre-oxidation and sintering time of 5 hours to obtain a pre-oxidized composite.

[0163] (3) Mixing the pre-oxidized composite with an oxygen supplement (lithium peroxide, the amount of lithium peroxide added is 1% based on the mass of the pre-oxidized composite) under nitrogen protection for 10 minutes to obtain a second mixture; placing the second mixture in a kiln and performing a pulse sintering in an oxygen atmosphere at a furnace pressure of 50 Pa; the pulse sintering steps include 950°C-2h→920°C-2h→950°C-2h→920°C-2h→950°C-2h→920°C-2h→950°C-2h→920°C-2h→910°C-4h to obtain a primary sintered product.

[0164] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.65 MPa and a grading frequency of 45 Hz to obtain a positive electrode material.

[0165] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Al 0.3 O2.

[0166] Comparative Example 1

[0167] The difference from Example 1 is:

[0168] (3) Mixing the pre-oxidized composite with an oxygen supplement (lithium peroxide, the amount of lithium peroxide added is 1% based on the mass of the pre-oxidized composite) under nitrogen protection for 10 minutes to obtain a second mixture; placing the second mixture in a kiln and sintering it once in an oxygen atmosphere at a furnace pressure of 50 Pa; the primary sintering temperature is 970° C., the primary sintering time is 12 hours, and a primary sintering product is obtained.

[0169] Figure 3 The SEM morphology of the positive electrode material provided in Comparative Example 1 of the present application is as follows: Figure 3 As shown, the chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.60 Co 0.1 Mn 0.3 O2, in which the doping elements are Zr, Al and Sr, and the coating elements are W and Ti. Since the amount of doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0170] Comparative Example 2

[0171] The difference from Example 1 is:

[0172] (3) placing the pre-oxidized composite in a kiln and performing a primary sintering in an oxygen atmosphere at a furnace pressure of 50 Pa; the primary sintering temperature is 950° C., the primary sintering time is 8 h, and a primary sintering product is obtained.

[0173] Comparative Example 3

[0174] The difference from Example 1 is:

[0175] (3) Mixing the pre-oxidized composite with an oxygen supplement (lithium peroxide, the amount of lithium peroxide added is 1% based on the mass of the pre-oxidized composite) under nitrogen protection for 10 minutes to obtain a second mixture; placing the second mixture in a kiln and sintering it once in an oxygen atmosphere at a furnace pressure of 50 Pa; the primary sintering temperature is 980° C., the primary sintering time is 12 hours, and a primary sintering product is obtained.

[0176] (4) The primary sintered product is subjected to air flow pulverization at an air pressure of 0.8 MPa and a grading frequency of 55 Hz to obtain a matrix material. The median particle size D50 of the matrix material is 2.9 μm ≤ D50 ≤ 3.3 μm.

[0177] Test method:

[0178] (1) Particle distribution test of positive electrode materials:

[0179] The SEM image of the positive electrode material was measured at a magnification of 3K by a scanning electron microscope, and the particle size in the SEM image was measured using Nana Measure software. 200 particles in the SEM image were randomly measured, and the average size of the longest diameter of the particles was obtained to be D, the average size of the wide diameter that perpendicularly bisects the longest diameter of the particles was L, and the average aspect ratio of the particles was α=D / L. The wide diameter is a straight line that perpendicularly bisects the longest diameter of the particles, and both ends of the straight line intersect with the edge of the particles.

[0180] (2) The proportion of particles with a particle size less than 1 μm in the positive electrode material

[0181] 1) Use a cotton swab to pick up a small amount of powder sample and apply it evenly and densely on the conductive glue; use a hair dryer to slowly blow in the direction where there are no other samples, and when it is confirmed to be evenly applied on the surface, blow strongly for more than 10 times until there is no residual powder;

[0182] 2) Set the basic conditions of SEM: voltage 5 kV, current 12 mA, magnification 2k, contrast and brightness are adjusted using the auto key, and the measurement position is set to the part with 400 to 1200 particles (center value 800 particles);

[0183] 3) Save the SEM image. Each sample is measured under this condition for 10 photos. All the pictures are imported into the software through Metis Vision software. The bottom size and border size of the SEM image are adjusted. Then, the particles with a size range of dmin-dmax, an aspect ratio of 0-9.0, and an area ratio of 0-1.00 are manually identified.

[0184] 4) The number of particles with a particle size of less than 1 μm in the positive electrode material is calculated as R%, and the number of particles with an aspect ratio of 1≤α≤1.6 in all particles is calculated as P%. In the SEM image of the positive electrode material, agglomerates are not included in the statistical particles of the aspect ratio. Agglomerates refer to large particles formed by agglomerating multiple particles.

[0185] (3) Test of metal elements in positive electrode materials:

[0186] Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool and dilute to a volume of 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times, and test the content of the main elements Li, Ni, Co, and Mn and the content of other elements such as doping elements by ICP. The determination is carried out using Agilent 5110ICP-OES detection equipment.

[0187] (4) 24-hour gas production value test:

[0188] The positive electrode material, binder, conductive agent and carbon nanotubes were mixed in a mass ratio of 96:2:1.5:0.5 to make positive electrode sheets, and graphite, conductive agent and binder were mixed in a mass ratio of 95.4:1.2:3.4 to make negative electrode sheets. The separator was Cellgard separator, and the electrolyte was an equal mixture of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. The batteries were assembled into 2Ah soft-pack batteries, and the gas production for 24 hours was tested by the drainage method.

[0189] (5) Particle size test:

[0190] The particle size distribution of the positive electrode material particles was obtained by using the laser diffraction light intensity distribution of the British Malvern Mastersizer 3000 model laser particle size analyzer. The volume-based cumulative particle size distribution of the particle size distribution determination was measured by the laser diffraction method, D 10 It indicates the particle size corresponding to the cumulative particle size distribution percentage of the powder reaching 10%, D 50 Indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D 90 It indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%.

[0191] Volume particle size distribution width of positive electrode material = (D 90 -D 10 ) / D 50 .

[0192] (6) Specific surface area test:

[0193] The specific surface area of ​​the material was calculated using the American TriStar II specific surface and pore analyzer by nitrogen adsorption and the BET method.

[0194] (7) Morphology test:

[0195] The Hitachi S4800 scanning electron microscope was used to observe the surface morphology, particle size, etc. of the samples, and the SEM image of the positive electrode material was obtained.

[0196] (8) Tap density test of positive electrode materials:

[0197] Test of tap density ρ1: Dandong Better BT-303 was used to test the tap density, with a vibration rate of 3000 times / min, a vibration time of 1min, and a vibration amplitude of 3mm±0.1mm.

[0198] (9) Compaction density test of positive electrode materials:

[0199] The compaction density ρ2 of the powder was tested using a compaction density meter with a pressure of 6t for 30s.

[0200] (10) Electrochemical performance evaluation using button half-cell:

[0201] The positive electrode material: conductive agent SP: binder (5% PVDF glue) = 93:5:2 mass ratio was mixed and homogenized, and then the slurry was evenly coated on a 16μm thick aluminum foil and placed in a 100℃ oven for drying for 12h. The negative electrode used a Li metal sheet with a diameter of 16mm and a thickness of 1mm, the diaphragm used a polyethylene porous membrane with a thickness of 20μm, and the electrolyte used an equal amount of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1mol / L LiPF6 as the electrolyte. The positive electrode plate, diaphragm, negative electrode plate and electrolyte were assembled into a 2016 button battery in an Ar gas glove box with a water content and an oxygen content of less than 5ppm.

[0202] Capacity test system: The blue electric test system was used for electrical performance testing (charge and discharge voltage was 3.0-4.4V, temperature condition was 25°C), 0.1C charging, 0.1C discharging, constant voltage cut-off current was 0.005C, and the discharge capacity C mAh / g and initial capacity were calculated based on the discharge capacity.

[0203] Cycle test system: 50 cycles of charge and discharge at 1C rate at 55°C and charge and discharge voltage of 3.0-4.4V. The ratio of the final capacity to the initial capacity after 50 cycles is the 50-cycle capacity retention rate, which is the high-temperature cycle performance. It should be noted that the cut-off current of the capacity test is consistent with the constant voltage cut-off current in the above capacity test system.

[0204] The positive electrode materials of the above embodiments (abbreviated as S1 to S13) and comparative examples (abbreviated as D1 to D3) were subjected to physical and chemical performance tests and electrochemical tests. The test results are shown in Tables 1 and 2 below.

[0205] Table 1 Physical and chemical properties of cathode materials

[0206]

[0207] Table 2 Electrochemical performance results of positive electrode materials

[0208]

[0209] According to the test data of Examples 1 to 13, while controlling the average aspect ratio of the positive electrode material particles, the number of particles with a diameter of 1 μm is controlled within a suitable range. These particles with a diameter of less than 1 μm can be effectively filled between particles larger than 1 μm, which can improve the compaction density and capacity of the positive electrode material. The particles with a large number and good roundness can reduce the particle breakage of the positive electrode material and improve the structural stability and long cycle performance of the positive electrode material. Under the synergistic effect of the two, the positive electrode material has both high capacity and energy density, and excellent long cycle stability, especially high temperature cycle stability.

[0210] According to the test data of Example 1 and Examples 2 to 6, as the content of nickel in the positive electrode material increases, the capacity of the positive electrode material gradually increases. By controlling the appropriate primary pulse sintering temperature, the roundness of the positive electrode material particles is improved, so that the aspect ratio of the particles can be controlled within the range of 1 to 1.6, and the cycle performance of the positive electrode material is more stable. Among them, the positive electrode material of Example 6 has the highest nickel content, which leads to an increase in the lattice distortion of the positive electrode material and a decrease in the structural stability of the positive electrode material, so the cycle capacity retention rate of the positive electrode material decreases.

[0211] According to the test data of Example 1 and Example 7, as the pre-oxidation sintering temperature and time increase, the lithium ions can be fully embedded in the pre-oxidation composite to form a stable nickel cobalt manganese oxide compound. After the lithium ions are fully embedded, during a pulse sintering, the adhesion of some particles caused by the lithium salt as a flux can be effectively avoided, so that the particles of the sintered matrix material are more rounded and dispersed, and the positive electrode material has excellent cycle performance and capacity performance.

[0212] According to the test data of Example 1 and Example 8, due to the shortening of the pre-oxidation sintering time, part of the lithium salt can act as a flux, resulting in more particle adhesion, thereby increasing the aspect ratio of the particles, reducing the roundness of the particles, and some particles are easily broken during the electrode rolling process, resulting in more side reactions between the positive electrode material and the electrolyte, and the capacity and cycle retention rate of the positive electrode material are reduced compared to Example 1.

[0213] According to the test data of Example 1 and Example 9, since the positive electrode material prepared in Example 9 is a nickel cobalt aluminum lithium compound, the discharge capacity of the positive electrode material decreases slightly, and the cycle capacity retention rate of the positive electrode material can be maintained at a high level.

[0214] According to the test data of Example 1 and Example 11, it can be seen that the number of repetitions of the first stage and the second stage in a single pulse sintering process increases, the particle aspect ratio of the positive electrode material is further reduced, the proportion of particles below 1 μm is further reduced, and since the air pressure and grading frequency of the airflow crushing of the primary sintering product are increased, the particle size distribution width of the positive electrode material is increased, the compaction density of the positive electrode material is increased, and the specific capacity and cycle retention rate of the positive electrode material are also improved.

[0215] According to the test data of Example 1 and Example 12, due to the decrease in the amount of oxygen supplement added, the proportion of particles satisfying 1≤α≤1.6 in all particles decreases, the number of slender particles in the positive electrode material increases, and the specific capacity and cycle retention rate of the positive electrode material decrease slightly.

[0216] According to the test data of Example 1 and Comparative Example 1, since the pulse sintering process is not adopted and the sintering temperature is relatively high, the number of small particles is reduced, and the high-temperature sintering easily causes the particles to grow too large, resulting in a further increase in the aspect ratio; the number of particles below 1 μm decreases, resulting in more gaps between the particles of the positive electrode material after the electrode plate is coated, and the compaction density is relatively low, resulting in low capacity; at the same time, the contact of a large amount of electrolyte increases the number of side reactions on the surface of the material, further resulting in a decrease in the battery cycle performance.

[0217] According to the test data of Example 1 and Comparative Example 2, since the pulse sintering process is not adopted, the sintering temperature is low, and no oxygen supplement is added, the positive electrode material particles do not grow sufficiently, the reaction is insufficient, the aspect ratio of the particles increases, and the roundness of the particles decreases; the number of particles below 1 μm accounts for an increased proportion, the specific surface area of ​​the positive electrode material is relatively large, the residual alkali on the surface increases, the side reactions with the electrolyte increase, and the cycle performance and discharge capacity of the positive electrode material decrease.

[0218] According to the test data of Example 1 and Comparative Example 3, since the pulse sintering process is not adopted, the sintering temperature is low, and no oxygen supplement is added, the positive electrode material particles do not grow sufficiently, the reaction is insufficient, the aspect ratio of the particles increases, and the roundness of the particles decreases; the number of particles below 1 μm accounts for an increased proportion, the specific surface area of ​​the positive electrode material is relatively large, the residual alkali on the surface increases, the side reactions with the electrolyte increase, and the cycle performance and discharge capacity of the positive electrode material decrease.

[0219] Figure 4 The following is a comparison chart of the positive electrode material cycle performance provided by Example 1 of the present application and Comparative Example 1 and Comparative Example 2, as shown in FIG. Figure 4 As shown, the capacity retention rate of the positive electrode material of Example 1 after 50 cycles of charge and discharge at a rate of 1C is better than that of the positive electrode materials prepared in Comparative Examples 1 and 2.

[0220] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes a plurality of particles; The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the wide diameter that perpendicularly divides the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.6; In addition, the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, and 10≤R≤16.

2. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.5≤a≤0.98, 0<b≤0.40, 0<c≤0.4, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al; the M element includes at least one of Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.

3. The positive electrode material according to claim 1, characterized in that In the positive electrode material, the number of particles satisfying 1≤α≤1.6 accounts for β in all particles, and β≥90%.

4. The positive electrode material according to claim 1, characterized in that The volume median particle size D50 of the positive electrode material is 2.0 μm to 6.0 μm; and / or the volume particle size distribution width of the positive electrode material satisfies: 1.0<(D 90 -D 10 ) / D 50 ≤2.

5. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, the particles include primary particles, and the particle size of the primary particles is 1 μm to 5 μm.

6. The positive electrode material according to claim 1, characterized in that The specific surface area of ​​the positive electrode material is 0.4 m 2 / g~0.8m 2 / g.

7. The positive electrode material according to claim 1, characterized in that The tap density of the positive electrode material is ρ1g / cm 3 , 1.5≤ρ1<2.2; and / or, the compaction density of the positive electrode material is ρ2g / cm 3 , 3.0≤ρ2<3.

5.

8. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies 11≤pH≤12.

9. The positive electrode material according to claim 1, characterized in that The button-type battery made of the positive electrode material has a capacity cycle retention rate of ≥95% after 50 cycles at 55°C.

10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Battery monomer, battery device, power utilization device and energy storage device

    CN119993979A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN119993979B

  • Positive electrode material and battery

    WO2026138632A1